Associations of circulating cell-free microRNA with vasculopathy and vascular events in systemic lupus erythematosus patients. (2nd January 2019) - Kay, SD; Carlsen, AL; Voss, A; Burton, M; Diederichsen, ACP; Poulsen, MK; Heegaard, NHH
Abstract : Objective : Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a high risk of atherosclerosis and cardiovascular disease (CVD). MicroRNAs (miRNAs) are small non-coding RNAs that modulate protein translation, and dysregulation is seen in autoimmunity, atherosclerosis, and CVD. We investigate associations between circulating miRNAs and markers of atherosclerosis in SLE patients. Method : A group (n = 121) of well-characterized SLE patients were screened for atherosclerosis by cardiac computed tomography and carotid ultrasound. RNA was purified from plasma and 46 specific miRNAs were determined using quantitative real-time polymerase chain reaction. Results : Forty-one miRNAs were consistently detected. Fifty out of 118 available SLE patients had atherosclerosis. A profile consisting of three miRNAs (decreased miR-125b, miR-101, miR-375) was indicative of atherosclerosis. Multivariate logistic regression identified eight clinical manifestations associated with atherosclerotic outcome. The full classification profile showed a specificity of 88% and a sensitivity of 86%. Hierarchical clustering identified an eight-miRNA profile that differentiated a subgroup of SLE patients (n = 16) who had significantly increased venous thrombotic events (p = 0.045), a higher prevalence of β2 -glycoprotein I antibodies (p = 0.029), and an increased prevalence of thrombocytopenia (p = 0.028). Conclusion : In this cross-sectional study, the circulating miRNA profile distinguished SLE patients with atherosclerosis from those without. Furthermore, an eight-miRNA signature was associated with thrombocytopenia, venous thrombotic events, and β2 -glycoprotein I antibodies in SLE patients. Prospective studies are needed to confirm the findings and to establish the precise role of circulating miRNA profiling in the evaluation of atherosclerosis in SLE.